Interleukin 6 –174 G/C polymorphism: its relation to coronary artery disease and circulating IL-6 levels – a systematic review and meta-analysis. (14th October 2021) - Rai, H; Colleran, R; Cassese, S; Joner, M; Kastrati, A; Byrne, R A
Abstract: Introduction: Circulating IL-6 levels and at least one polymorphic form of IL6 gene (IL6 –174 G/C, rs1800795) have been found to be independently associated with coronary artery disease (CAD). However, the association status of this polymorphism with CAD remains unclear. Purpose: We conducted a systematic review and updated meta-analysis to comprehensively ascertain the association status of IL6 –174 G/C with CAD and its effect on the levels of circulating IL-6 in humans. Methods: Comprehensive online search was undertaken to find relevant case-control/cohort studies investigating the association of IL6 –174 G/C with CAD. The association status of –174 G/C with CAD amongst pooled sample as well as separately amongst different ancestral populations was assessed. Association of –174 G/C with circulating IL-6 levels was also assessed amongst pooled sample as well as separately for CAD cases and CAD-free controls. Study-level odds ratios (OR) and 95% confidence intervals (CI) were pooled by Mantel-Haenszel fixed-effects models. Results: Quantitative synthesis for assessing the role of this polymorphic variant in CAD was performed using 55 separate qualifying studies with a collective sample size of 51, 213 (19, 160 cases / 32, 053 controls). The pooled association of –174 G/C with CAD was found to be statistically significant through dominant (OR= 1.15, 95% CI= 1.05–1.25, p=0.002) as well as allelic genetic model comparisons (OR= 1.13, 95% CI= 1.06–1.21, p=0.0003). Asian and Asian-Indian ancestral subgroups showed significant association with CAD in both genetic model comparisons (OR range= 1.29 to 1.53, p value range ≤0.02). Other ancestral subgroups did not show any meaningful association. Circulating IL-6 levels were found to be significantly higher amongst the "C" allele carriers in the pooled sample (Standard mean difference, SMD= 0.31, 95% CI= 0.01–0.22 pg/ml, p=0.009) as well as the CAD-free control subgroup (SMD= 0.10, 95% CI= 0.02–0.17 pg/ml, p=0.009). CAD case subgroup did not show any significant association (p=0.12). Conclusions: The present systematic review and meta-analysis confirms an association between IL6 –174 G/C polymorphism residing in the IL6 gene and CAD, especially amongst Asian and Asian-Indian ancestral groups. Upregulation of plasma IL-6 levels in the "C" allele carriers seem to be at least partly responsible for the observed association. Further investigations with large structured case-control studies amongst these ancestral groups are warranted. Funding Acknowledgement: Type of funding sources: None.